Thermal properties of ternary tellurite glass system. - Mohamed Kamari , Halimah; Wan Yusoff, Wan Mohamad Daud; Abd. Aziz, Sidek; Mustafa, Iskandar Shahrim; Abd. Wahab, Zaidan; Matori, Khamirul Amin (Malaysian Solid State Science and Technology Society (MASS), 2011)
Ternary tellurite glass system of [(TeO2)60 (B2O3)40]1 y[Ag2O]y glasses had been synthesized by melt quenching method. The thermal expansion coefficient of the glasses was determined between 30oC and 210oC. Experimental results indicate that the thermal expansion varies with micro structural of the glass system. Transition temperature and Debye temperature decrease with Ag2O due to loose packing of the glass network.